Pesantren Sunan Drajat: Educational Dynamics, Cultural Evolution, and Social Transformation - Nashihin Nashihin; Nuruddin Nuruddin; Putu Eka Wirawan (GHAITSA : Islamic Education Journal, 2026)
Pondok pesantrens, as institutions providing religious education, have also been impacted by the Covid-19 pandemic, requiring adjustments to their educational services to maintain the quality of religious instruction. This study aims to assess the extent of the Sunan Drajat Lamongan Pondok pesantren's role in supporting students, ensuring that their achievements in religious education are sustained. The research employs a qualitative approach, utilizing case studies, observations, literature reviews, in-depth interviews, and small group discussions to gather data.The findings of the study indicate that the learning environment and social setting at the Sunan Drajat Lamongan Pondok pesantren are highly conducive. By fostering a positive atmosphere and a strong sense of belonging among the students, the pesantren enables students to easily receive spiritual guidance, develop their character, and accelerate the internalization of social values. Consequently, Pondok pesantrens, as a social education system, are able to produce future religious leaders who excel academically, grow personally, and make valuable contributions to society.